Applying a gender lens in cervical cancer programming: the assessment of sexually active young men involvement in cervical cancer preventive efforts - Nkosi, Chimwemwe Nyambose (2021)
Cervical cancer remains a public health concern across the world especially in developing countries including Malawi. Much as country’s policies calls for male involvement in sexual reproductive health, their involvement in cervical cancer prevention is still not clear. Sexually active young men are usually left behind despite their important role in its prevention.The study’s main objective was to assess the involvement of sexually active young men in cervical cancer preventive efforts in Lilongwe Urban. This was mixed methods study. A sample of 196 randomly selected study participants and 10 key informants were interviewed. Inclusion criteria were sexually active young men aged 15 to 24 patronising Bwaila and Kawale health centres. Thematic analysis was used for qualitative data and analysed using NVivo 7.4 software. Quantitative data was analysed using STATA version 14 statistical program. The study findings suggest knowledge of causes of cervical cancer, partner’s risks and whether one is circumcised or not as having a significant impact on young men involvement in cervical cancer preventive efforts. Their non-involvement is attributed to a number of factors which includes structural barriers in terms of access to cervical cancer information and services, lack of a standalone policy, lack of access points of the services such as youth-friendly health corners. Culturally, the misconception that cervical cancer is a feminine disease and men as sole decision makers also deters them from assessing the services.The study findings suggest low involvement of sexually active young men in cervical cancer prevention despite their willingness and their important role in the disease prevention. Deliberate efforts therefore have to be put in place to involve them if the disease is to be contained. The study suggests their involvement in policy and programme formulation as well as implementation and integration of cervical cancer in youth friendly health services as some of the strategies that could be employed to increase their involvement